The growing relevance of the PPSA in the Brazilian exploration and production arena and its main challenges. (28th February 2019) - Brito, Thiago da Cunha
Abstract: This article presents an analysis of how the changes introduced in the pre-salt regulatory framework positively affected the interest of foreign companies in investing in the exploration and production of oil and natural gas in Brazil, revitalizing competitiveness in the last pre-salt bidding rounds that occurred during 2017 and 2018. In addition, the article discuss the growing importance of Pré-sal Petróleo S/A (PPSA) in the production sharing regime, supported by the commercial declaration of the Mero field and the consequent start of the production phase in this field, the quantity of unitization agreements involving PPSA, as well as the new contracts signed over the past two years. Finally, taking into account the pre-structured stage of PPSA, some risks and challenges related to human resources, internal processes and the use of information technology were underlined, which the company should address to fulfil its legal obligations in an expected level of efficiency, quality and performance.